THE EFFECTIVENESS OF USING COOPERATIVE SCRIPT METHOD TO IMPROVE STUDENTS’ READING COMPREHENSION ON RECOUNT TEXT OF 8THGRADE STUDENTS OF SMP N KEWAPANTE, MAUMERE IN ACADEMIC YEAR 2017/ 2018 - Janggo, Wandelinus Oscar (Universitas Wiralodra, 2018)
This research is entitled ?The Effectiveness of Using Cooperative Script Method to Improve Students? Reading Comprehension on Recount Text of 8th Grade Students of SMP N Kewapante, Maumere in Academic Year 2017/ 2018?. The objective of this research is to investigate and to find out whether the use of cooperative script method effective to improve students? reading comprehension on recount text. The method of this research is experimental research especially quasi experimental research. In analyzing the data, the researcher combined both quantitative and qualitative data analysis. In qualitative data analysis, the researcher used interview technique in order to get information about students? perceptions in reading, while in quantitative data analysis, the researcher used SPSS version 16. The result of the research showed that the implementation of Cooperative Script Method in experimental class was more effective to help the students in reading comprehension on recount text compared to the use of the conventional method in control class of the eighth grade students of SMP N Kewapante, Maumere. It is also found that cooperative script method positively contributed to improve students? reading comprehension. Therefore ,the researcher  suggests the teachers to use cooperative script method in order to improve students reading comprehension Additionally, cooperative script method can also motivate students to be more active, relax and enthusiastic to comprehend reading texts.